Synergy of Lean and Green for Improving Small-Scale Agroindustry Performance - Muslikah Desti Kurniasari; Nafis Khuriyati; Wagiman Wagiman (APTA and DTIP FTP UGM, 2020)
Small Medium Enterprises (SMEs) play an important role in the economy of Indonesia. It contributed to the 21.20% of national total economy. Global competition is a challenge and an opportunity for SMEs including agroindustry sector. Therefore, it is needed for strengthening their competitiveness. In the midst of this effort, the raising concern about environment issue has increased. This research aims to determine the alternatives or options in production aspect based on lean and green for small-scale crackers industry. Sustainable Value Stream Mapping (SVSM) was applied to describe the production condition and identify wastes from lean and green point of view. Furthermore, Value Stream Analysis Tools (VALSAT) and Life Cycle Impact Assessment (LCIA) were used to analyze waste throughout the production activity. The results show that the small-scale cracker industry has already implemented synergy of lean and green, however some alternatives for reducing lead time and waste are needed such as demand forecasting and improvement of working methods